PRODUKSI SERBUK KALSIUM KARBONAT DENGAN MESIN PENGGERUS HASIL MODIFIKASI PADA PT SUGIH ALAMANUGROHO - Wahyuningsih, Tri; Probowati, Dyah; Hermanto, Olivia Silvi; Asworo, Monika; Setyawan, Meindra (Jurnal Teknologi Mineral dan Batubara, 2023)
Limestone is a sedimentary rock formed naturally from the died marine organisms. Limestone is used in various industrial fields, such as paint, plastics, carpets and soil pH regulator industries. PT. Sugih Alamanugroho is a limestone mining and calcium carbonate powder producer company. To produce calcium carbonate powder, limestone is dried, comminuted, and classified by size. The drying process reduces moisture content less than 4%. Then, the limestone is crushed by a jaw crusher and followed by secondary crushing by means of a hammer mill. The results of the secondary grind are crushed again using a modified grinding machine. Calcium carbonate powder will pass through an 800-mesh screen into the cyclone collector using a blower. In the cyclone collector, 800-mesh powder falls into the bottom of the cyclone, while 1200-mesh powder comes out of the cyclone and enters the cloth bags. The position of the feed on the side of the modified grinding machine is able to reduce collisions with the product. From the entire production steps, calcium carbonate powder products were produced, but did not meet the production amount target due to obstacles that occurred in the form of power outages, replacement of spare parts or equipment maintenance, machine breakdowns and late availability of spare parts.